Physicochemical characteristics, microbiological safety and sensory acceptability of coconut dregs during fermentation using Rhizopus oligosporus - N. K., Rosni; M., Sanny; N. S. A., Bahranor; Y., Rukayadi (Rynnye Lyan Resources, 2020)
The aims of this study were to determine the changes in physicochemical characteristics, microbiological safety and sensory acceptability of coconut dregs during fermentation using Rhizopus oligosporus. Fermentation of coconut dregs was done using Rhizopus oligosporus as a starter culture for three days (fresh coconut dregs was used as control). The control sample is fresh dregs without any process while other samples will through fermentation. The physicochemical analyses included internal temperature, pH, total soluble solids (TSS), water activity (aw), colour, proximate analysis and texture profile. Microbiological analyses included total plate count (TPC), Escherichia coli, Salmonella spp., Pseudomonas aeruginosa, Bacillus cereus, Staphylococcus aureus and LAB. Sensory acceptability was also carried out. The results showed that internal temperatures and TSS were increased and the pH decreased throughout the fermentation. The aw showed no changes. The colour of fermented coconut dregs had a higher percentage in lightness compared to yellowness and redness which showed that the colour of fermented dregs still maintains the white colour. A gradual increased in hardness, springiness, cohesiveness, chewiness and resilience was observed. Moisture content, crude fat and protein increased while ash and crude fibre decreased but no changes in carbohydrate throughout the fermentation. The results for microbial count showed the reducing number of S. aureus and B. cereus while increasing number of TPC and LAB. Interestingly, E. coli, Salmonella spp. and P. aeruginosa was not detected in fermented and non-fermented coconut dregs. The non-fermented coconut dregs were preferred more by the panellists as it obtained the highest score in term of colour, odour, texture and overall acceptability on sensory attributes evaluation.